Financial Policy of the Roman Governor towards Provincial Communities during Period of the Principate - Sergey V. Telepen (RUDN Journal of World History)
The area of responsibility of the governor of the province was to perform both commanding, judicial and fiscal duties. The latter had to replenish the treasury with tax revenues from the provinces. The governors needed funds to maintain the military troops accommodated in the province. Besides that, at least by the beginning of the 2nd century ensuring the financial stability of the provincial communities themselves became an important area. It was controlled by the governor. Tendance about the welfare of provincial cities is reflected, in particular, in the correspondence of Pliny the Younger with Trajan, the speeches of Dion Chrysostom as well as epigraphic documents of a legal nature. This and a number of other sources reflect various ways to maintain the financial well-being of communities by reducing the local taxes, lump-sum contributions and various unproductive expenses. In this regard, the Antonins’ is marked by a turn in the financial strategy of the Roman state towards the “humanization” of the provincial policy. Monitoring of city finances was an aspect that required the constant attention to the state of income and expenditure of provincial communities. At the same time, the viceroy was not limited to the personnel resources of his staff but tried to involve the local aristocracy, endowing its representatives with control and judicial powers, acting, however, in the context of the customs and practices evolved in each individual community.